2021
DOI: 10.1111/ijd.15573
|View full text |Cite
|
Sign up to set email alerts
|

Combination of topical and oral glutathione as a skin‐whitening agent: a double‐blind randomized controlled clinical trial

Abstract: Background The antimelanogenesis effect of topical and oral glutathione has been shown in several in vitro and clinical studies. However, whether combination of topical and oral glutathione is superior to topical or oral monotherapy is unknown. This study aimed to compare the skin‐whitening effect of topical and oral glutathione combination therapy against topical and oral monotherapy. Methods This double‐blind randomized controlled study was done on 46 participants who were divided into two equal groups. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The results of its efficacy to treat melasma remain variable 128–131 . Wahab et al 128 in a double‐blind randomized controlled study involving 46 subjects found glutathione an effective skin‐lightening agent and a combination of topical and oral glutathione was superior than either route used alone. Another randomized, double‐blind, placebo‐controlled clinical trial comprising 124 Asian females demonstrated significant skin‐lightening and reduction in size of facial pigmentation after oral supplementation with combination of l‐cystine and l‐glutathione 129 .…”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of its efficacy to treat melasma remain variable 128–131 . Wahab et al 128 in a double‐blind randomized controlled study involving 46 subjects found glutathione an effective skin‐lightening agent and a combination of topical and oral glutathione was superior than either route used alone. Another randomized, double‐blind, placebo‐controlled clinical trial comprising 124 Asian females demonstrated significant skin‐lightening and reduction in size of facial pigmentation after oral supplementation with combination of l‐cystine and l‐glutathione 129 .…”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
“…Intravenously, it is usually given in a dose of 900 mg weekly or can be repeated 2–3 times a week. The skin whitening effect usually occurs as early as 2–3 weeks 128 . However, intravenous use of glutathione as skin whitening agent remains under‐evaluated and is banned by US FDA because of commonly reported adverse effects such as skin rashes, abdominal pain that may be severe, thyroid, and renal function derangement, Stevens–Johnson syndrome, and toxic epidermal necrolysis.…”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has previously demonstrated that healthy patients along with patients with HIV and Type 2 diabetes experience an increase in GSH levels, a reduction in oxidative stress, and improved immune function when GSH is carried out within liposomes and administered orally [12,13]. Topical formulations of GSH have been studied extensively on humans and animal models for their dermatological effects and exist commercially as a skin-brightening agent [14][15][16]. However, the effects of topical GSH application on modulating GSH levels and immune function have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%